1972
DOI: 10.1083/jcb.55.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adenosine 3'-5'-Cyclic Monophosphate on Cell Proliferation

Abstract: Secondary cultures of human diploid fibroblasts, which demonstrate density-dependent inhibition of cell growth, were used to study the effect of adenosine 3'-5'-cyclic monophosphate (cAMP) on cell proliferation. DNA synthesis in nonconfluent cultures and in contact-inhibited cultures stimulated to grow by refeeding with fresh medium was found to be inhibited by exogenous cAMP. The properties of this inhibition of DNA synthesis, together with the alterations in cAMP metabolism observed in confluent cultures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
1

Year Published

1973
1973
1977
1977

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(31 citation statements)
references
References 34 publications
3
27
1
Order By: Relevance
“…7) the observation that administration of fresh serum to serum-restricted cultures causes a drop in cAMP (14,17,18,26). The rapidity of this drop compared with the slow rise in cAMP upon serum starvation is remarkable.…”
Section: Methodsmentioning
confidence: 99%
“…7) the observation that administration of fresh serum to serum-restricted cultures causes a drop in cAMP (14,17,18,26). The rapidity of this drop compared with the slow rise in cAMP upon serum starvation is remarkable.…”
Section: Methodsmentioning
confidence: 99%
“…This has been variously reported as lying in G1 (7,13,14), in G2 (8), or in multiple discrete portions of the cycle (15, 16). These studies have in most cases used cell populations synchronized by techniques that possibly cause unbalanced growth, which might raise questions regarding the use of these materials for examining the effect of a growth regulatory substance.…”
Section: Introductionmentioning
confidence: 99%
“…Transformed cells have a lower cAMP content than untransformed cells (1,5). Exogenous cAMP analogs or the induction of endogenous cAMP slows or stops growth of some cells (6)(7)(8)(9)(10). Proliferation of contact-inhibited cells, induced by refeeding or proteolytic treatment, is prevented by cAMP analogs (7,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…162 production in the W138 cells (Kurtz et al, 1974;Kelly & Butcher, 1974;Makman et al, 1973). Froehlich & Rachmeler (1972) demonstrated that the addition of cyclic AMP or 6-N,2'-O-dibutyryl cyclic AMP inhibits cell division in human lung fibroblasts. We demonstrated that 8-methylthioadenosine 3': 5'-cyclic monophosphate (methylthio cyclic AMP), an analogue of cyclic AMP, has an effect very similar to that of PGE1 on the W138 cells in culture, in that it also inhibits cell division and the incorporation of [3H]thymidine into DNA (Polgar et al, 1975).…”
mentioning
confidence: 99%